Efficient ethylene copolymerization with polar monomers using palladium anilinonaphthoquinone catalysts. Issue 45 (2nd November 2018) - Ding, Lin; Cheng, Hailong; Li, Yanqing; Tanaka, Ryo; Shiono, Takeshi; Cai, Zhengguo
Abstract : Copolymerizations of ethylene with methyl acrylate (MA) and 5-norbornen-2-yl acetate (NBAC ) were explored using anilinonaphthoquinone-ligated palladium catalysts. Abstract : Copolymerizations of ethylene with methyl acrylate (MA) and 5-norbornen-2-yl acetate (NBAC ) were explored using anilinonaphthoquinone-ligated palladium catalysts. Ethylene copolymerization with MA afforded polar functionalized semicrystalline polyethylene with moderate activity (up to 55 kg mol −1 h −1 ) and considerable polar monomer incorporation (3.54 mol%). The palladium catalysts also conducted highly active (up to 356 kg mol −1 h −1 ) ethylene copolymerization with NBAC to produce polar functionalized cyclic olefin copolymers (COCs) with tunable polar monomer incorporation (36.1–81.1 mol%), which shows better NBAC incorporation than those reported previously. The introduction of sterically bulky substituents on the aniline ligand is effective for enhancing the tolerance of this catalytic system towards polar monomers. The thermal, mechanical, and surface properties of polar functionalized COCs were improved/modified by tuning polar monomer incorporation.